Structure and Function of the Soil Rhizosphere Fungal Communities in Medicinal Plants—A Preliminary Study - Itaii Applebaum; Mareeswaran Jeyaraman; Chen Sherman; Tirza Doniger; Yosef Steinberger (Agriculture, 2022)
Plants regulate their rhizosphere microbiome, which partly comprises the fungal community. We conducted a study in order to determine the effect that five medicinal plant species (Origanum syriacum, Salvia fruticosa, Teucrium capitatum, Myrtus communis and Pistacia lentiscus) have on the fungal community in their rhizosphere. We measured abiotic parameters and used sequencing to determine the structure of the rhizosphere fungal community, both taxonomically, as phyla and genera, and functionally, as trophic modes. Our data shows that the rhizosphere fungal communities were significantly different, both taxonomically and functionally. The rhizosphere of M. communis had a significant relative abundance of saprotrophs and a lower relative abundance of symbiotrophs than the control soil and the rhizosphere of T. capitatum. The relative abundance of the genus Aureobasidium was significantly higher in the rhizosphere of P. lentiscus than in the control and for all other rhizospheres, but that of S. fruiticosa. The relative abundance of genus Alternaria was lower in the rhizospheres of S. fruticosa and M. communis than in the control soil. Our results highlight the potential use of these plants in agroforestry, as a means to influence the soil fungi population.